Changes in global value chains and the Covid-19 pandemic - Jaklič, Andreja (Teorija in praksa, 2020)
The consequences of the Covid-19 pandemic might restrict the future development of global value chains (GVCs), especially impacting small and exportoriented economies. The article discusses factors of the resilience and stability of GVCs and identifies the most important structural changes that may deepen following the global pandemic and digitalisation. We apply a new measure of value chain participation that allows for the simultaneous examination of global and domestic integration of economies/industries into GVCs. Analysing the changes in value chain structure during the past recession may indicate the consequences of the current crisis. The past global recession shows a shortterm increase in the domestic value chain share that mirrors the reduction in the GVC share, as well as the relatively high stability of simple value chains in the EU and in Slovenia. However, several manufacturing sectors in Slovenia saw a high and permanent increase in the share of complex value chain in the post-crisis period, suggesting a mixed response of countries and industries depending on their resilience capability
Keywords: Crises; Economic policy; Ekonomska politika; Epidemics; Epidemije; Evropska unija; globalne verige vrednosti; GVV; Internacionalizacija; Internationalization; izvoz; Krize; odpornost in učinkovitost GVV; struktura verig vrednosti; tuji trgi; Value; Vrednost